LAPAROSCOPIC TRANSPERITONEAL URETEROURETEROSTOMY COMBINED WITH RETROGRADE FLEXIBLE URETEROSCOPY ASSISTANCE FOR URETERAL STRICTURE- CASE SERIES OF SEVEN PATIENTS - Deyan Anakievski (Peytchinski Publishing, 2021)
Most strictures of the ureters are detected and usually occur in the part of the ureter when the calculus has been trapped for a long time, after ESWL or as a complication of transureteral lithotripsy after the introduction of the holmium laser. The treatment of these strictures variesand depends on many parameters, the most important being the type of stricture, severity, length and location. In many cases, endoscopic treatment with stenting is the first choice of treatment performed retro or antegrade. In case of failure or contraindication for endoscopic treatment, ureteral reconstruction can be performed by open, laparoscopic or robotic techniques. Laparoscopic ureteroureterostomy is a preferred minimally invasive technique for the treatment of benign ureteral strictures.